TINJAUAN KRIMINOLOGI TERHADAP ANAK SEBAGAI PELAKU BEGAL SEPEDA MOTOR YANG MENGGUNAKAN SENJATA TAJAM (Studi Kasus Di Wilayah Hukum Kepolisian Resort Palu) - Moh Ihsan; Muliadi Muliadi (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
One form of crime that often happens in every region and that is often discussed is begal by using a motorized vehicle. This crime is identified with various cases of violence on the streets, but in the Big Indonesian Dictionary, the word